Extracranial-Intracranial High-Flow Bypass with Internal Carotid Artery Ligation at Neck for Giant Cavernous Internal Carotid Artery Dissecting Aneurysm in a Teen Girl with Postoperative Unusual Complication of Mono-ocular Blindness: A Case Report - Chowdhury, Forhad H.; Ekramullah, Sheikh Mohammod; Khalil, Mohammod Ibrahim; Arifin, Mohammod Shamsul (Indian Journal of Neurosurgery, 2019)
Extracranial-intracranial (EC-IC) high-flow bypass with internal carotid artery (ICA) ligation at the neck is an important treatment option for giant cavernous ICA dissecting aneurysm. Such treatment may be associated with many complications. We report a case that developed postoperative mono-ocular blindness. So far to our knowledge such complication has not been reported in the literature. A 14-year-old girl presented with recent headache, eye ache, occasional double vision, and occasional right-sided visual impairment. Neurologic examination revealed no abnormality. Computed tomographic (CT) scan of the head showed a large, right parasellar, and mostly hyperdense space-occupying lesion. CT angiogram of the brain showed giant dissecting aneurysm of right-sided cavernous segment ICA. A right-sided external carotid artery–radial artery graft–middle cerebral artery (ECA-RAG-MCA [M2]) high-flow bypass was done with ligation of the right ICA in the neck. Postoperatively, the patient developed complete, mono-ocular, and permanent blindness on right side. Mono-ocular blindness is a serious complication from ophthalmic/central retinal artery thrombosis in high-flow EC-IC bypass with ICA ligation. Strategy is required to find and to set for its prevention.
Keywords: extracranial-intracranial high-flow bypass; giant cavernous internal carotid artery dissecting aneurysm; radial artery graft; mono-ocular blindness